A Scientometric Study of Oral Medicine Articles from Iran Published in PubMed-Indexed Journals - Mortazavi, Hamed; Faraji, Mehdi; Namdari, Mahshid; Hatami, Amir Masoud; Vardiani, Mina; Fatemi Sovini, Sina; Gholipur, Mahdieh (Journal of Dental School, 2020)
Objectives This study aimed to scientometrically assess the oral medicine articles from Iran published in PubMed-indexed journals. Methods In this descriptive cross-sectional study, the author information section of PubMed database was electronically searched for oral medicine articles published from the beginning of 2006 to the beginning of 2016 with at least one author from Iran using the keywords “oral medicine”, “oral and maxillofacial medicine”, “stomatology”, “stomatologist”, and “Iran”. The results were reported as frequency, and trend analysis was performed. Results A total of 280 oral medicine articles published from the beginning of 2006 to the beginning of 2016 were found to have at least one author from Iran, which comprised 2.9% of the entire articles in this field. The majority of published articles were original articles (77%) followed by case reports (15%), review articles (5%), short communications (2%) and letter to editors (1%). The majority of articles had been published in J Dent Res Dent Clin Dent Prospects (18%), followed by J Dent (Tehran) (6.7%), and J Contemp Dent Pract (5.5%). The trend of publication of articles was ascending during this time period except for the year 2011. The frequency of articles had a significantly ascending trend during the aforementioned time period (P=0.004). Conclusion From the beginning of 2006 to the beginning of 2016, Iran’s share of oral medicine articles published in PubMed-indexed journals was around 3% and had an ascending trend